The Effect of Internet-Based Applications on Written Communication Skills - Hakimeh Davoodi; Mohsen O.Jaghi (Journal of Business, Communication and Technology, 2024)
Despite its theoretical importance, there is a scarcity of experimental research into the effectiveness of internet-based applications in the English classroom context. The present study, using a mixed-methods design, aimed at examining whether online applications, including Adobe Connect and BigBlueButton, could improve writing. In doing so, a pool of 34 pre-intermediate students participated in the study based on convenience sampling, and a pool of six students participated in the qualitative phase of the study based on purposive sampling. IELTS task 2 band descriptor and semi-structured interviews were used to gather the data. One-way ANCOVA, theme-based categorization, and inter-coder reliability were conducted to analyze the data. The results confirmed that there was a statistically significant difference between the two experimental groups; the Adobe Connect group showed higher scores than the BigBlueButton group with respect to written communication skills. Following inter-coder reliability, ten common themes were elicited from the interviews, including innovative, fruitful in learning collocations, challenging, useful for distance learning, colorful, and bad internet connection. Ultimately, practical implications were provided for students and teachers.